Artificial Intelligence Enhanced Extended Reality as Part of Ship Commissioning - Rajamäki, Joni (My University, 2025)
Ship commissioning refers to the process of testing and validating the systems onboard a vessel and leads up to the handing over of the ship to the customer. A shipbuilding project consists of vast amounts of contractors, subcontractors and suppliers, and the commissioning of ships is reliant on engineers navigating documentation and manuals from each of these parties. It is estimated that a single hour of sea trials costs a shipyard as much as 32 000 euros. As such, every minute spent unnecessarily shifting through documentation is needlessly expensive. Extended reality technologies present a new paradigm of human computer interaction, and can be utilized to present data in revolutionary ways. Industrial extended reality solutions have traditionally leaned towards using optical see through devices, rather than video passthrough capable ones, due to video passthrough technology being lacking until recently. Modern video passthrough has seen significant improvements over the last years, and should be considered as a candidate for industrial extended reality solutions. Artificial intelligence is another technology, which has seen breakthroughs in the recent times. Artificial intelligence can be utilized to compound large sets of information, such as technical documentation related to ship commissioning, and distinguish the relevant parts. This work aims to evaluate the viability of artificial intelligence enhanced extended reality solutions as industrial tools for ship commissioning. In order to evaluate these technologies, a proof of concept is developed, and then tested via user testing. The test users are linked with the shipbuilding industry as either shipbuilding professionals or as researchers. Analysis of the testing revealed, that the recent advancements in both artificial intelligence and extended reality show promising potential for applications in shipbuilding and ship commissioning. The performance of the extended reality platform and the quality of the artificial intelligence enhancements reached the expectations for an industrial tool for ship commissioning.
Keywords: Artificial Intelligence, Augmented Reality, Extended Reality, Shipbuilding, Ship Commissioning